The development of the criminal law of evidence in the Netherlands, France and Germany between 1750 and 1870 : from the system of legal proofs to the free evaluation of the evidence - Bloemberg, Ronnie (Legal history library ;, 2020)
"This book describes the development of the criminal law of evidence in the Netherlands, France and Germany between 1750 and 1870. In this period the development occurred that the so-called system of legal proofs was replaced with the (largely) free evaluation of the evidence. The system of legal proofs, which had functioned since the late middle ages, consisted of a set of strict evidentiary rules which predetermined when a judge could convict someone. In this book an explanation is given of the question why between 1750 and 1870 the strict evidentiary rules were replaced with the free evaluation of the evidence. The thesis of this research is that the reform was induced by a change in the underlying epistemological and political-constitutional discourses which together provided the ideas which inspired a significant reform of the criminal law of evidence"--